Teaching History as a Part of Social Studies at Secondary Level (Surkhet Journal, 2025)
The study explores the strategies used by teachers in different phases of teaching: planning, implementation and evaluation phase of teaching historical part of Social Studies and the students’ participation in teaching and learning of history part of Social Studies. This study followed qualitative approach to study. In order to explore the participants’ experience of teaching history part of Social Studies, the phenomenological design was followed as study design. The interview and semi structure interview were used as tools of data collection. The collected data were analyzed descriptively in order to derive the conclusion. The finding of this study was that most of the Social Studies teachers followed traditional teaching approaches and methods in teaching of history part. Their teaching was heavily based on delivery of textbook content and completion of textbook exercise. The teachers were not found not being up to date in teaching methods and techniques. Traditional methods, techniques and activities made teaching of history part of social studies boring. This study suggests teaching ways of history should be modified and different activities and resource materials prescribed in curriculum should be followed while teaching of history in the classroom. In this ways, teacher and students ' active participant situation may find and how to improve them.